PERAN LIFE STYLE DALAM MEMODERASI PENGARUH PROMOSI DAN BRAND IMAGE TERHADAP MINAT BELI DAN KEPUTUSAN PEMBELIAN PADA ROTI BAKAR BANDUNG BONDOWOSO DI SITUBONDO - Syama, Nur Izzuddien; Karnadi, Karnadi; Fandiyanto, Randika (Jurnal Mahasiswa Entrepreneurship (JME), 2024)
Roti Bakar Bandung Bondowosois micro/small/medium enterprises (MSMEs) engaged in the culinary field. Roti Bakar Bandung Bondowoso is known to have good product quality and comfortable taste, so it is liked by many people who already know it. This study aims to analyze the role of Lifestyle in moderating the influence of Promotion and Brand image on buying interest and purchasing decisions for Roti Bakar Bandung Bondowoso in Situbondo. The data collection method uses quantitative methods and nonprobability sampling, with purposive sampling being the method technique. This study's data analysis and hypothesis testing used the Structural Equation Model - Partial Least Square (PLS-SEM). The results of direct influence hypothesis testing using the Smart PLS 3.0 application show that promotion significantly positively affects buying interest. Brand image has a significant positive effect on purchase intention. Promotion has a significant positive impact on purchasing decisions. Brand image has a significant positive effect on buying decisions. Promotion moderated by Lifestyle has a positive but insignificant impact on purchasing decisions. Promotion of purchasing decisions through buying interest has a significant positive effect. The promotion of purchasing decisions through buying interest has a significant positive impact. Brand image on purchasing decisions through buying interest has a significant positive effect.